Konsep Birokrasi Korupsi di Indonesia dalam Teori Bureaucratic Oversupply Model - Alifia Nurshadrina Hermawan; Alvika Jienni Mulia Pangestuti; Bunga Aulia Salsabila Putri (Universitas Islam Balitar, 2025)
This writing analyzes the phenomenon of corruption in the Indonesian bureaucracy using a normative juridical approach and bureaucratic oversupply theory. This research aims to understand the concept of bureaucracy, opportunities for corruption in bureaucracy, and efforts to prevent it. The research results show that corruption in the Indonesian bureaucracy is still a serious problem caused by various factors, both internal and external. Bureaucratic oversupply theory provides a deeper understanding of how bureaucratic structure and behavior can create conditions conducive to corruption. This research concludes that to overcome the problem of corruption, comprehensive bureaucratic reform is needed, including strengthening supervision, improving the quality of human resources, and implementing good governance.